2019
DOI: 10.3390/w12010107
|View full text |Cite
|
Sign up to set email alerts
|

Research on Forward Osmosis Membrane Technology Still Needs Improvement in Water Recovery and Wastewater Treatment

Abstract: Forward osmosis (FO) has become an evolving membrane separation technology to recover water due to its strong retention capacity, sustainable membrane fouling, etc. Although a good deal of research has been extensively investigated in the past decades, major challenges still remain as follows: (1) the novel FO membrane material properties, which significantly influence the fouling of the FO membranes, the intolerance reverse solute flux (RSF), the high concentration polarization (CP), and the low permeate flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 137 publications
0
22
0
Order By: Relevance
“…Therefore, the FO process requires additional operations to continuously or effectively regenerate the draw solution. In addition, the FO process in the FO–RO hybrid system can be beneficial in terms of freshwater recovery and enhanced pollutants removal (e.g., organic matter, scaling precursors and boron) [ 129 , 130 ]. It has been demonstrated that a FO hybrid process shows potential for desalinating water; for example, a FO–RO hybrid plant built in South Korea with a capacity of 2000 m 3 /day utilised an FO step to dilute seawater from an inlet solute mass fraction ( w b,in ) of 0.034 to a range of 0.010–0.013, reducing energy consumption by up to 25% compared with traditional SWRO [ 131 ].…”
Section: Hybrid Ro Desalination Systemsmentioning
confidence: 99%
“…Therefore, the FO process requires additional operations to continuously or effectively regenerate the draw solution. In addition, the FO process in the FO–RO hybrid system can be beneficial in terms of freshwater recovery and enhanced pollutants removal (e.g., organic matter, scaling precursors and boron) [ 129 , 130 ]. It has been demonstrated that a FO hybrid process shows potential for desalinating water; for example, a FO–RO hybrid plant built in South Korea with a capacity of 2000 m 3 /day utilised an FO step to dilute seawater from an inlet solute mass fraction ( w b,in ) of 0.034 to a range of 0.010–0.013, reducing energy consumption by up to 25% compared with traditional SWRO [ 131 ].…”
Section: Hybrid Ro Desalination Systemsmentioning
confidence: 99%
“…These membranes have shown reduce ICP and have high porosity and a strong pore structure [62]. The use of nanomaterials within the support layer of various types of FO membranes has with been proven to strengthen the membrane's structure, increase water flux, and reduce ICP [63]. Other materials are being incorporated into FO membranes, such as aquaporin (AQP).…”
Section: • Surface Blending and Graftingmentioning
confidence: 99%
“…An ideal DS would be stable, inexpensive, and accessible, provide high osmotic pressure, offer efficient recovery methods, have low toxicity, and deliver high water flux. DS can be separated into categories [63] [35,65]. Sodium chloride is the most commonly used DS since it is inexpensive, accessible, very soluble, and allows for high osmotic pressure [66].…”
Section: Draw Solutions For Fomentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been a couple of review papers in recent years concerning the basic principles of FO [21][22][23][24], draw solutions [22,[25][26][27][28][29][30][31], applications [21,25,27,[32][33][34][35][36][37][38][39], (bio)fouling [22,25,26,30,[40][41][42][43][44][45][46], membrane fabrication [19,23,30,35,39,43,47,48], or upscaling [49,50], we, for the major part of this review, discuss the challenges of FO evidences from various literatures to prove the unreliability of the existing structural parameter approaches. In addition, we will highlight that, beyond a certain water permeability, the true bottleneck is the mechanical support of the membrane instead of the selective membrane layer.…”
Section: Introductionmentioning
confidence: 99%